1996
DOI: 10.1002/chem.19960020414
|View full text |Cite
|
Sign up to set email alerts
|

Pulled Molecular Strings and Stacked Molecular Decks: Chelate‐Ring Formation vs. Metal–Metal Bridging in Dicopper(I) Complexes of 2,2′‐Bipyrimidine with Diphosphine Ligands of Variable Polymethylene Chain Length

Abstract: Abstract:The "self-assembly" reaction troscopic results for the dissolved species polymethylene chain length 1s reduced between bischelating 2,T-bipynmidine, indicate a strained configuration in the one notch further to n = 5 (5), the diphosmetallic copper, Cu2+, and two equiva-case of complex [(p-bpym)Cu,{p-Ph,Pphines can no longer bridge but help to lents of bidentate Ph,P(CH,),PPh, pro-(CH,),PPh,),J2+ (6) with n = 6 Once the form eight-membered chelate rings (strucduces crystallographically characterized tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 52 publications
(20 citation statements)
references
References 45 publications
0
20
0
Order By: Relevance
“…Herein we demonstrate the first synthesis of 2,2′‐bipyridine (bpy)‐containing monomers for ring‐opening metathesis polymerization (ROMP), the coordination of ruthenium or palladium by the pendant bpy, the subsequent functionalization of the metal center with multidentate ligands, and finally the ROMP of these monomers in nonpolar solutions with ruthenium‐based initiators. Multidentate nitrogen‐donor ligands are advantageous ligands because they are often neutral and stable in solution and form highly stable complexes with numerous transition metals 1–16. The resulting multidentate nitrogen‐donor ligand‐based metal complexes have a large number of potential applications.…”
Section: Introductionmentioning
confidence: 99%
“…Herein we demonstrate the first synthesis of 2,2′‐bipyridine (bpy)‐containing monomers for ring‐opening metathesis polymerization (ROMP), the coordination of ruthenium or palladium by the pendant bpy, the subsequent functionalization of the metal center with multidentate ligands, and finally the ROMP of these monomers in nonpolar solutions with ruthenium‐based initiators. Multidentate nitrogen‐donor ligands are advantageous ligands because they are often neutral and stable in solution and form highly stable complexes with numerous transition metals 1–16. The resulting multidentate nitrogen‐donor ligand‐based metal complexes have a large number of potential applications.…”
Section: Introductionmentioning
confidence: 99%
“…Reacting 1 with the copper(I) precursor [Cu(NCCH 3 ) 4 ](BF 4 ) in 1:1 or 2:1 ratio gave a complex with the composition [Cu( 1 ) 2 ](BF 4 ) = ( 4 )(BF 4 ) (Scheme ). The crystal structure analysis revealed that this compound shows no chalcogen coordination but adopts the familiar bis(α‐diimine)copper(I) structure with a chelate‐distorted tetrahedral coordination at the metal (Figure , Table and Table S3, Supporting Information). Compound 1 thus acts only as a bidentate chelate ligand towards Cu I due to the weakness of Cu I –O bonds, especially with uncharged central oxygen atoms.…”
Section: Resultsmentioning
confidence: 99%
“…An important area of research using copper complexes of α‐diimines involves their photochemical activity and their suitability to act in topologically non‐trivial molecules,, culminating in the recognition, analysis and the specific development of molecular machines …”
Section: Introductionmentioning
confidence: 99%
“…23 The complex dications of {(µ-L)[IrCl(C 5 Me 5 )] 2 } 2ϩ were isolated in only one configuration according to the 1 H-NMR spectra; by analogy and considering the typically smaller metal-metal distances d < 5.1 Å in abpy-bridged dimers 12,14 relative to bpym-bridged dinuclear species (ca. 5.6 Å) 24 we assume these to be the anti isomers (Fig. 2).…”
Section: Synthesis and Configurationmentioning
confidence: 99%